Tokenizing coopetition in a blockchain for a transition to circular economy - Narayan, Rumy; Tidström, Annika (Elsevier, 2020)
The circular economy offers a way for businesses to conceptualize sustainable economic activity with a concern for environmental and societal well-being. Putting this concept into practice is a complex undertaking, given the current production and consumption systems, and necessitates strategies that enable competition and cooperation between various actors to generate and scale up the best ideas. Simultaneous competition and cooperation, or coopetition, is studied in strategy literature within the context of managing the complexity of business networks. Coopetition could offer valuable perspectives for firms transitioning to circular models. The purpose of this paper is to show how coopetition could be operationalized and optimized using tokens in a blockchain to support a transition to circular models of value creation and appropriation. The findings of our study indicate that tokens could enable previously disconnected product ecosystems to converge and unleash the waves of creativity and innovation required for circular business models. However, facilitating such convergence would require the coopetition models to transition from comprising the current stages of value creation and appropriation to being based on value creation and circulation.
Keywords: sustainable; circular economy; coopetition; blockchain; token; economy; enterprises; business; cooperation (general); value creation; networking (making contacts); circular economy; innovations; strategic planning; development (active); competition (activity); fi=Johtaminen ja organisaatiot|en=Management and Organization|